2022
DOI: 10.3390/cancers14225676
|View full text |Cite
|
Sign up to set email alerts
|

Activated Eosinophils Predict Longer Progression-Free Survival under Immune Checkpoint Inhibition in Melanoma

Abstract: Immune checkpoint inhibition (ICI) has yielded remarkable results in prolonging survival of metastatic melanoma patients but only a subset of individuals treated respond to therapy. Success of ICI treatment appears to depend on the number of tumor-infiltrating effector T-cells, which are known to be influenced by activated eosinophils. To verify the co-occurrence of activated eosinophils and T-cells in melanoma, immunofluorescence was performed in 285 primary or metastatic tumor tissue specimens from 118 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…This value seems a little low, but we referred to a previous paper that reported eosinophil count as a biomarker for ICI treatment; cutoff value was 100 cells/μL in urothelial carcinoma and 130 cells/μL in melanoma. 10,18 Vaios et al reported that a high eosinophil count is associated with better PFS in patients receiving bevacizumab treatment for glioblastoma, which supports our findings. 28 Since there were reports that changes in eosinophil counts affect the prognosis of ICI treatment, we examined changes in eosinophil counts and prognosis, but they did not prove to be prognostic factors.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This value seems a little low, but we referred to a previous paper that reported eosinophil count as a biomarker for ICI treatment; cutoff value was 100 cells/μL in urothelial carcinoma and 130 cells/μL in melanoma. 10,18 Vaios et al reported that a high eosinophil count is associated with better PFS in patients receiving bevacizumab treatment for glioblastoma, which supports our findings. 28 Since there were reports that changes in eosinophil counts affect the prognosis of ICI treatment, we examined changes in eosinophil counts and prognosis, but they did not prove to be prognostic factors.…”
Section: Discussionsupporting
confidence: 90%
“…The normal eosinophil count is generally set at 100–300 cells/μL, and cutoff value of eosinophil we determined in the ATZ/BEV group was 170 cells/μL. This value seems a little low, but we referred to a previous paper that reported eosinophil count as a biomarker for ICI treatment; cutoff value was 100 cells/μL in urothelial carcinoma and 130 cells/μL in melanoma 10,18 . Vaios et al .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Mechanistically, microarray analysis using RNA isolated from eosinophils under ICI treatment in melanoma revealed that Wnt signaling prolongs the survival of activated eosinophils 34 . Activated eosinophils accumulate in tumor tissues, indicating that tumor‐infiltrating eosinophils eliminate cancer cells via vascular normalization and macrophage polarization 35–37 . Thus, despite reports on the functional analysis of eosinophils under ICI treatment, the detailed underlying mechanisms by which eosinophils are increased in peripheral blood and infiltrate into tumors have not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%